Impact of Rheumatoid Arthritis and Its Management on Falls, Fracture and Bone Mineral Density in UK Biobank - Clynes, Michael A.; Jameson, Karen; Prieto-Alhambra, Daniel; Harvey, Nicholas C.; Cooper, Cyrus; Dennison, Elaine M. (Frontiers in Endocrinology, 2019)
Objectives. The aim of this study was to investigate associations between rheumatoid arthritis (RA), RA medications and bone mineral density, falls and fractures, using UK Biobank data. Methods. Diagnosis of RA was made using Hospital Episode Statistics (HES) ICD-10 coding. We assessed RA relationships with estimated bone mineral density (eBMD) from heel quantitative ultrasound measurements, self-reported falls (in last year) and HES recorded fracture, adjusted for age, ethnicity, BMI, smoking status and physical activity. Results. Of 502,543 participants, 3849 (1.4%) of women and 1643 (0.7%) of men had a diagnosis of RA. Median age of the participants was 57 years (IQR 50 - 63) in women and 58 (IQR 50 - 64) in men. RA was associated with lower eBMD (men: β -0.244, 95% CI -0.378, -0.110 p<0.001; women: β -0.217, 95% CI -0.297, -0.138 p<0.001) a reported fall in the last year (men: OR 1.54, 95% CI 1.26, 1.87 p<0.001; women: OR 1.36, 95% CI 1.19, 1.56 p<0.001) and fracture in women (OR 1.76, 95% CI 1.43, 2.16 p<0.001). Corticosteroid therapy in men (β -0.934, 95% CI -1.565, -0.304 p=0.004) and disease modifying anti-rheumatic drug (DMARD) use in both sexes (men: β -0.437, 95% CI -0.761, -0.112 p=0.008; women: β -0.243, 95% CI -0.421, -0.065 p=0.007), but not biologic therapy, were associated with a lower eBMD with RA. Conclusions. RA was associated with lower eBMD, increased falls and fracture. Corticosteroid and DMARD therapy, but not biologic therapy, were associated with lower eBMD.